Interplay between environmental factors, articular involvement, and HLA-B27 in patients with psoriatic arthritis. Issue 1 (January 1992) - Scarpa, R; Del Puente, A; di Girolamo, C; della Valle, G; Lubrano, E; Oriente, P
Abstract : Medical records of 138 patients with psoriatic arthritis and 138 with rheumatoid arthritis were reviewed for the occurrence of an environmental factor triggering arthritis. Twelve (9%) of the patients with psoriatic arthritis had had an acute disorder immediately preceding onset of arthritis (an operation in four cases, articular trauma in three, abortion in two, myocardial infarction, thrombophlebitis, and phosphoric ester intoxication in one case each). Peripheral arthritis occurred in all these patients. Among the rheumatoid patients, an acute event immediately preceding the onset of the disease was recorded in two cases (1%) only (chi 2 = 7.52; p = 0.006). No significant association was found in the arthritic patients between the incidence of acute events preceding arthritis onset and positivity of the HLA-B27 phenotype.